PHARMACOEPIDEMIOLOGY AND THE EFFICACY OF ANTIHYPERTENSIVE TREATMENT IN REAL-LIFE PRACTICE OF THE CARDIOLOGY REFERRAL CLINIC - A. V. Kontsevaya; T. S. Romanenko; V. A. Vygodin; S. B. Fitilev (Столичная издательская компания, 2015)
Arterial hypertension is a disease which leads to severe negative social and economic consequences. Pharmacoepidemiologic studies allow assessment of present situation on high blood pressure (BP) treatment and search of ways of its efficacy improvement.Aim. To study treatment of hypertensive patients who had visited the cardiology referral clinic for the first time and to assess treatment dynamics over the following 6 months with the estimation of its efficacy.Material and methods. The study included two steps. At the first step a primary sample of the study participants was formed out of hypertensive patients who had visited for the first time a cardiologist in one of the Moscow district cardiologic dispensary in 2010 with the further completion of expert cards in accordance with the primary medical documentation (n=1766). At the second step the phone survey was conducted 6 months after the first visit with the completion of special questionnaires (n=1419).Results. Recommendations for antihypertensive treatment given to the cardiologic dispensary patients are in line with the current guidelines, and 6 months after the first visit 91% of the patients had continued antihypertensive treatment. However, the efficacy of BP control turned out to be low: target BP level was only detected in 28.8% of the patients, and 36.7% of the respondents developed hypertensive crises during the 6 months.Conclusion. Despite the follow-up in the referral clinic and the intake of the prescribed drugs the patients revealed low efficacy of BP control. The reasons for this fact require further investigation. Probably, the improvement of BP control requires implementation of special education and motivational techniques as short-term contact with specialists does not lead to high efficacy of antihypertensive treatment.